Effect of agri-environment schemes (2007–2014) on groundwater quality; spatial analysis in Bavaria, Germany. (April 2022) - Tzemi, Domna; Mennig, Philipp
Abstract: Degradation of groundwater quality and contamination of drinking resources is one of the most widespread and harmful impacts of over-fertilisation in agriculture. As part of the Common Agricultural Policy (CAP), agri-environment schemes (AES) have as main objective the protection and management of the farm environment, including groundwater quality. In this article a spatial econometric model is applied to evaluate the impact of AES on groundwater nitrate concentrations. Bavaria, a federal state of Germany, is used as a case study, due to the findings of high nitrate concentrations in the groundwater. A significantly negative effect is found between AES expenditures focusing on grassland management and nitrogen concentrations, while AES focusing on crop management, organic farming and preservation of cultural landscape did not show a significant effect. The assessment of other factors such as cereals and forage showed a statistically positive effect on nitrate concentrations. However, loam soil texture, rainfall, and residential area were found to negatively affect nitrate concentrations. Highlights: AES focusing on grassland measures can be effective in reducing nitrate levels. AES focusing on crop production, organic farming, cultural landscape showed no significant effect on groundwater quality. Cereal crops and forage showed a positive effect on groundwater quality. High levels of nitrates in the groundwater are concentrated in cropland areas rather than grasslands.